Rancang Bangun Sistem Informasi Katering Berbasis Web Menggunakan Code Igniter - Yaowita, Irvan; Budi, Akhmad (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
One of the basic human needs is food for consumption. The food consumed can be divided into 2 types, firstly is food that must be cooked and secondly is food that can be consumed directly without cooking. Families can get cooked food by cooking the desired food themselves. Apart from that, cooked food can also be obtained by buying food in canteens, cafetaria, restaurants or catering. Food obtained from canteens, cafetaria and restaurants is generally obtained by purchasing directly on site. Meanwhile, food obtained from catering is generally obtained by ordering a menu from the catering business. The ordered menu can be a single menu or a package menu. Mentari Catering aims to optimize the use of information technology so that customers have the freedom to order the food offered. The aim of this research is to build a web site-based information system to manage orders from Mentari catering customers. The system development method used in this research is the waterfall model. In this research too, CodeIgniter is used to create web applications quickly and easily. The result of this research is a website-based system to make it easier for catering customers to order both package menus and single menus. Apart from that, customers can also provide testimonials about the food menu and services provided. Testimonials can be a consideration for potential customers who want to order.